THE TALE OF THE DUELING NEUROSURGEONS : THE HISTORY OF THE HUMAN BRAIN AS REVEALED BY TRUE STORIES OF TRAUMA, MADNESS, AND RECOVERY - Kean, Sam, (LITTLE, BROWN AND COMPANY, 2014)
Early studies of the human brain used a simple method: wait for misfortune to strike--strokes, seizures, infectious diseases, horrendous accidents--and see how victims coped. In many cases their survival was miraculous, if puzzling. Observers were amazed by the transformations that took place when different parts of the brain were destroyed, altering victims' personalities. Parents suddenly couldn't recognize their own children. Pillars of the community became pathological liars. Some people couldn't speak but could still sing. Sam Kean explains the brain's secret passageways and recounts forgotten tales of the ordinary people whose struggles, resilience, and deep humanity made modern neuroscience possible.--From publisher description